NARRATIVE STRATEGIES FOR REVIEW BRAND NAME BAGS ON PLATFORM TIKTOK - Sukwitchai, Chanita; Kumsubha, Bhanond; Fyeted, Kajohn (Journal of MCU Nakhondhat, 2024)
This research aim to study strategies for Narrative Strategies for Review Brand Name Bags on Platform TikTok. selected channels. This research is qualitative research. The analysis focused on 40 clips by analyzing 10 clips per channel from 4 channels. Selecting the clips with the highest views, top 10 from 2022 - 2023. Consists of Dr. Brandname, Sevendayy_brandname, houseoflux.th and Brandname_exchange. Data were collected by using study and research documents related to concepts and theories. And used to analyze by using Content Analysis examining various components and interpreting the marketing communication of designer handbags. Key aspects analyzed included product quality, high pricing, scarcity, emotional appeal, symbolic value, and brand history. The research findings on the narrative methods for reviewing luxury brand Name bags on platform TikTok platform revealed the following 1) There is a story structure where the content is initially introduced (In Medias Res). Additionally, there is a framework explaining features, advantages, and benefits of usage (Features - Advantages - Benefits) and various storytelling methods linking to a common theme (Petal Structure). Furthermore, the formal attire of characters in each channel includes suits and black gloves during reviews. 2) Characters positioning themselves as experts are distinctly present in the Dr. Brandname channel, using semi - formal language reflecting the essence of high - quality Brand Name Bags products and limited accessibility. Characters positioning themselves as sellers in houseoflux.th, Brandname_exchange, and Sevendayy_ brandname channels use informal language reflecting the essence of pricing and easy access to purchasing Brand Name Bags bags. Moreover, in the Dr. Brandname channel, a character (third person) demonstrates bag usage. Finally, characters with real usage experience are prominently featured in the Sevendayy_brandname channel, where bag reviews are done by customers who have directly purchased products from the store.